Antimicrobial Resistance of Salmonella enterica Serovar Typhimurium in Shanghai, China - Wang, Jinyan; Li, Yongrui; Xu, Xuebin; Liang, Beibei; Wu, Fuli; Yang, Xiaoxia; Ma, Qiuxia; Yang, Chaojie; Hu, Xiaofeng; Liu, Hongbo; Li, Hao; Sheng, Chunyu; et al. (Frontiers in Microbiology, 2017)
We aimed to analyze the antimicrobial resistance phenotypes and to elucidate the molecular mechanisms underlying resistance to cephalosporins, ciprofloxacin, and azithromycin in Salmonella enterica serovar Typhimurium isolates identified from patients with diarrhea in Shanghai. The isolates showed high rates of resistance to traditional antimicrobials, and 20.6%, 12.7%, and 5.5% of them exhibited decreased susceptibility to cephalosporins, ciprofloxacin and azithromycin, respectively. Notably, 473 (84.6%) isolates exhibited multidrug resistance (MDR), including 161 (28.8%) isolates that showed an ACSSuT profile. Twenty-two MDR isolates concurrently exhibited decreased susceptibility to cephalosporins and ciprofloxacin, and 6 of them were co-resistant to azithromycin. Of all the 71 isolates with decreased susceptibility to ciprofloxacin, 65 showed at least one mutation (D87Y, D87N, or D87G) in gyrA, among which 7 isolates simultaneously had mutations of parC (S80R) (n=6) or parC (T57S/S80R) (n=1), while 49 isolates with either zero or one mutation in gyrA contained plasmid-mediated quinolone resistance (PMQR) genes including qnrB, qnrS, and aac(6’)-Ib-cr. Among the 115 cephalosporin-resistant isolates, the most common ESBL gene was blaCTX-M, followed by blaTEM-1, blaOXA-1 and blaSHV-12. Eight subtypes of blaCTX-M were identified and blaCTX-M-14 (n=22) and blaCTX-M-55 (n=31) were found to be dominant. To the best of our knowledge, this is the first report of the presence of blaCTX-M-123 and blaCTX-M-125 in S. Typhimurium. Besides, mphA gene was identified in 15 of the 31 azithromycin-resistant isolates. Among the 22 isolates with reduced susceptibility to cephalosporins and ciprofloxacin, 15 contained ESBL and PMQR genes. Coexistence of these genes lead to the emergence of MDR and the transmission of them will pose great difficulties in S. Typhimurium treatments. Therefore, surveillance for these MDR isolates should be enhanced.